2021
DOI: 10.1108/ilt-03-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and information entropy analysis of frictional vibration signals in running-in progress

Abstract: Purpose This study aims to reconstruct the frictional vibration signal from noise and characterize the running-in process by frictional vibration. Design/methodology/approach There is a strong correlation between tangential frictional vibration and normal frictional vibration. On this basis, a new frictional vibration reconstruction method combining cross-correlation analysis with ensemble empirical mode decomposition (EEMD) was proposed. Moreover, the concept of information entropy of friction vibration is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Unlike the vibration signals, the low-frequency band dominated the spectrum of the sound pressure signals and caused a periodic variation in the waveform, as shown in Figure 3c,d. Meanwhile, the Pearson correlation coefficient was used to describe the correlation between two kinds of signals [21,22]. The Pearson coefficients were −0.03, −0.06, −0.05 and −0.07, respectively, which demonstrated that the original vibration and sound pressure signals were less correlated at each time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the vibration signals, the low-frequency band dominated the spectrum of the sound pressure signals and caused a periodic variation in the waveform, as shown in Figure 3c,d. Meanwhile, the Pearson correlation coefficient was used to describe the correlation between two kinds of signals [21,22]. The Pearson coefficients were −0.03, −0.06, −0.05 and −0.07, respectively, which demonstrated that the original vibration and sound pressure signals were less correlated at each time.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the "weak" FIV components in vibration and sound are correlated, which makes it possible to identify "weak" FIV by cross-correlation analysis (CCA) without the help of the friction coefficient. Of course, the discussion of detecting "weak" FIV signals by CCA is in no sense new, for example, see [21,22]. However, most of the present work focused on the CCA of the vibration signals in the tangential and normal directions rather than the vibration and sound signals.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the information entropy of mechanical friction vibration signals is closely related to the change of friction coefficient. This relationship can be used to monitor and evaluate the running-in process and wear state of machinery [ 26 , 27 ]. Ying et al proposed a rolling bearing fault diagnosis algorithm that utilizes ensemble entropy, the Holder coefficient theory, and the grey relation algorithm.…”
Section: Introductionmentioning
confidence: 99%